Globalization and Economic Development: Impact of Social Capital and Institutional Building - Cheng, Ming Yu; Mittelhammer, Ron (WILEY-BLACKWELL PUBLISHING, 2008)
Countries engaged actively in globalization have experienced phenomenal changes in economic, social, cultural, political, and technological progress. Some countries have benefited significantly from greater integration, while others have held globalization accountable for their economic failure and instability. Globalization introduces new political and social challenges. Benefiting from globalization requires complementary institutions and social development to deal with the changes and risks introduced by greater openness. This article examines whether globalization benefits economic development and how the developing countries could gain from globalization through their social capital and institutional building.